Characteristics of spicy food consumption and its relation to lifestyle behaviours: results from 0.5 million adults. (19th May 2021) - Wen, Qiaorui; Wei, Yuxia; Du, Huaidong; Lv, Jun; Guo, Yu; Bian, Zheng; Yang, Ling; Chen, Yiping; Chen, Yan; Shi, Liya; Chen, Junshi; Yu, Canqing; et al.
Abstract: This study aimed to describe the characteristics and lifestyle differences of spicy food consumption in 0.5 million adults. Participants were recruited from 2004 to 2008 in the baseline research of the CKB study. Higher frequency and stronger pungency degree in spicy food positively correlated with preference for salty taste, eating snacks/deep-fried foods, tea/alcohol drinking and tobacco smoking. Among weekly tea/alcohol drinkers and current regular smokers, participants with a higher frequency of spicy food consumption or preference for stronger pungency degree were more likely to prefer strong tea, drink alcohol exceed the healthy amount, drink alcohol in the morning every day, smoke ≥ 40 cigarettes per day, consume a larger amount of tea leaves, alcohol and cigarettes each day, and start habitual tea/alcohol drinking or smoking at an earlier age. Differences existed in lifestyle factors related to major chronic diseases according to spicy food consumption frequency and pungency degree among the Chinese population.